Analysis of bullying behavior experienced by street children - Fadhilah, Farah; Netrawati, Netrawati (Universitas Negeri Padang, 2022)
Street children are children who are forced to take to the streets due to a number of factors. The situation of street children is sometimes exacerbated by physical, verbal, emotional and sexual violence against children. Violence that occurs in the child's environment often occurs in the form of bullying. Bullying incidents do not only occur in the school environment, but also in the street children's environment. This study aims to analyze the types of bullying experienced by street children in the city of Padang. This research uses a type of qualitative research with a case study method. Sources of data in this study were street children as research subjects, as well as additional information in the form of research informants. Data collection methods used in this study were interviews and observation. The data analysis technique used refers to the interactive analysis model from Miles and Huberman. To test the validity of the data, the technique used is triangulation with sources. The results showed that the types of bullying experienced by street children in the city of Padang, namely direct bullying, in the form of being hit, pushed, tripped over, thrown things, teased, humiliated, humiliated, grabbed, compassed, pulled by his clothes, beaten up, cursed at, and slapped. For this type of indirect bullying, in the form of being expelled from social groups, spreading rumors, being insulted via the internet and being threatened via the internet. It can be concluded that every street child experience different types of bullying.